FEATURES OF THE DEVELOPMENT OF INTERNET MARKETING AT THE PRESENT STAGE - U.A Sharipova (Scholar Express Journals, 2023)
With the growth of the economy, there is increased competition in the market. For enterprises and organizations, the issue of survival is acute. This situation forces firms to look for new effective forms of promotion and positioning of their goods (services). The digital revolution opens up new opportunities and prospects for consumers and organizations, and it is safe to say that consumers today are much more "mobile".
Keywords: digital revolution; mobile; consumers and organizations